I MPL E ME NTA SI PRO GRA M L ITER A SI A L - Q UR’ A N DALAM PEMBINAAN KARAKTER RELEGIUS SISWA DI SD NEGERI 2 DALAM KAUM KECAMATAN SAMBAS TAHUN PELAJARAN 2023/2024 - Hendra Gusri Alvando; Mujahidin, Sera Yuliantini (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
The objectives of this research are: 1) To describe the planning of the Al- Qur'an literacy program at SD Negeri 02 Dalam Kaum in developing students' religious character. 2) To describe the implementation of Al- Qur'an literacy at SD Negeri 02 Dalam Kaum in developing students' religious character. 3) To describe the implementation of Al-Qur'an literacy at SD Negeri 02 Dalam Kaum in developing students' religious character. Researchers used a qualitative approach with descriptive research type. The data collection techniques used were observation, interviews and documentation. The data analysis techniques used are data reduction, data display, and conclusions. The research results show that: 1) Planning for the Al-Qur'an literacy program in training students' religious character at SD Negeri 2 in Kaum Sambas District for the 2023/2024 academic year, namely, the school principal determines the objectives of Al-Qur'an literacy, determines the method, and the media to be used. 2) Implementation of the Al-Qur'an literacy program in training students' religious character at SD Negeri 2 in Kaum Sambas District for the 2023/2024 academic year, namely, starting 15 minutes before lessons start by teachers who teach in class from Monday to Saturday, using the Al- Qur'an as a medium and using the grouping method. 3) embedding the Al- Qur'an literacy program in the religious character training of students at SD Negeri 2 in Kaum Sambas District for the 2023/2024 academic year, namely, students become more fluent in reading the Al-Qur'an and students' character becomes better, like students more ethical towards teachers and friends, more trustworthy in carrying out the responsibilities given, more honest and more disciplined, and the school environment becomes more conducive